Diagnostic accuracy and interobserver variability of Dynamic Vascular Pattern (DVP) in primary liver malignancies - A simple semiquantitative tool for the analysis of contrast enhancement patterns - Schellhaas, B.; Waldner, Maximilian; Goertza, R. S.; Vitali, Francesco; Kielisch, Ch.; Pfeifer, Lukas; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Wildner, Dane (Clinical Hemorheology and Microcirculation, 2017)
Contrast-enhanced ultrasound (CEUS) is a valuable tool in the diagnostic approach of focal liver lesions, but occasionally subjective and observer-dependent. Semiquantitative evaluation of dynamic CEUS (DCEUS) with standardised software programmes such as Dynamic Vascular Pattern (DVP) could help to improve diagnostic accuracy and objectivity in liver tumour assessment.The present study aimed at evaluation of diagnostic accuracy of DVP in a clinical setting.DVP images of 52 focal liver lesions [30 hepatocellular carcinomas (HCCs), 15 intrahepatic cholangiocellular carcinomas (ICCs), 7 focal nodular hyperplasias (FNHs)] were analysed by four blinded observers with different levels of CEUS-experience. Diagnostic accuracies for the assessment of dignity and entity were evaluated.Mean sensitivity, specificity, positive and negative predictive value for detection of malignancy with DVP were 48.4% /67.8% /92.7% and 29.3%, respectively. Total diagnostic accuracies for dignity/entity were 63.9% /38.5% (HCC: 58.3% /25.8%; ICC: 73.3% /50%; FNH: 67.9% /67.9%). Interreader-agreement was moderate (?= 0.42-0.58). Differential diagnosis between ICC and HCC was most challenging.Although developed to improve diagnostic accuracy and objectivity in the assessment of focal liver lesions, DVP alone seems insufficient for differential diagnosis of HCC, ICC and FNH and cannot replace the skills of an experienced observer.
EVALuna2:14711